2008
DOI: 10.1007/s10560-008-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Psychosocial Rehabilitation: Clinical Outcomes for Youth with Serious Emotional Disturbance Living in Foster Care

Abstract: Children living in foster care are an especially vulnerable population who often come to the attention of Medicaid mental health providers. These children experience a high incidence of emotional and behavioral disorders and may have specialized treatment needs related to their living arrangement status. This study assessed whether Children's Psychosocial Rehabilitation could effectively treat youth with severe emotional and behavioral disorders who live in foster care. Analysis of data from an open trial of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Combined with home practice assignments Pathways Home [ 54 ] Interpersonal USA Children: Foster care Age: 5–12 years Adults: Biological parents 32 weeks Trained consultants Not specified Parenting curriculum to prevent reunification failure by supporting development of a safe and nurturing environment. Booster sessions to fine-tune skills Promoting First Relationships [ 139 ] Interpersonal USA Children: Foster care Age: 10–24 months Adults: Biological parents 10 weeks Community mental health agencies Biological parent home Brief manualised sessions (60–75 min weekly) with video feedback, worksheets and handouts Psychosocial rehabilitation [ 166 ] Intrapersonal; Interpersonal USA Children: Foster care Age: 3–18 years 12–24 months Children’s psychosocial rehabilitation specialists Foster care placement Home support offering individualised family-focused and child-centred treatment (4–8 h per week), in addition to specialist support to relevant adults (2 h per week) Sanctuary Model [ 162 ] Intrapersonal USA Children: Residential care Age: 12–20 years 12 weeks Residential care staff Residential care placement Psychoeducational curriculum. Technical assistance from residential care staff.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with home practice assignments Pathways Home [ 54 ] Interpersonal USA Children: Foster care Age: 5–12 years Adults: Biological parents 32 weeks Trained consultants Not specified Parenting curriculum to prevent reunification failure by supporting development of a safe and nurturing environment. Booster sessions to fine-tune skills Promoting First Relationships [ 139 ] Interpersonal USA Children: Foster care Age: 10–24 months Adults: Biological parents 10 weeks Community mental health agencies Biological parent home Brief manualised sessions (60–75 min weekly) with video feedback, worksheets and handouts Psychosocial rehabilitation [ 166 ] Intrapersonal; Interpersonal USA Children: Foster care Age: 3–18 years 12–24 months Children’s psychosocial rehabilitation specialists Foster care placement Home support offering individualised family-focused and child-centred treatment (4–8 h per week), in addition to specialist support to relevant adults (2 h per week) Sanctuary Model [ 162 ] Intrapersonal USA Children: Residential care Age: 12–20 years 12 weeks Residential care staff Residential care placement Psychoeducational curriculum. Technical assistance from residential care staff.…”
Section: Resultsmentioning
confidence: 99%
“…(2013) [ 54 ] Promoting First Relationships USA Oxford, Marcenko, et al . (2016) [ 139 ] Psychosocial rehabilitation USA Williams, Sherr (2009) [ 166 ] Sanctuary Model USA Rivard, Bloom, et al . (2003) [ 162 ] Solution Focused Parenting Group (SFPG) Canada Triantafillou (2002) [ 102 ] Triantafillou (2002) [ 102 ] SuppOrting Looked after children In Decreasing Drugs, and alcohol (SOLID) UK Alderson, Kaner, et al .…”
Section: Resultsmentioning
confidence: 99%
“…I successfully implemented the dose-effect study (Williams, 2009b), and in collaboration with fellow clinicians wrote a treatment manual (Williams, Richards, Priest, Stockett, & Thompson, 2009), and developed and preliminarily validated a treatment fidelity measure for our program (Williams, Oberst, Campbell, & Lancaster, 2011). We examined whether certain populations benefited as much from the intervention as others (Williams & Sherr, 2009) and whether the program exhibited long-term effects on children's daily functioning (Williams & Downloaded by [York University Libraries] at 21:03 16 November 2014 Sherr, 2008). All of these were planned efforts to gradually evaluate and empirically inform our child PSR program model.…”
Section: First Steps and Initial Successmentioning
confidence: 99%
“…Living alone is related to high levels of depressive symptoms and low levels of well-being (Fransson et al, 2016; Hughes and Waite, 2002). Children who live in foster care are susceptible to increased rates of mental health problems, such as emotional and behavioral disorders (Sawyer et al, 2007; Williams and Sherr, 2009). Nduwimana et al (2016) investigated the effects of living in a foster family on the mental health of children in rural Rwanda and found that the number of symptoms of depression and anxiety faced by foster children is more than that experienced by non-foster children.…”
Section: Introductionmentioning
confidence: 99%